Pengaruh sifat machiavellian dan komitmen profesional terhadap intensi melakukan whistleblowing - Indra, Salsabila Ardelia; Kusumastuti, Ratih; Rahayu, Rahayu (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study was conducted to examine the causes or factors that influence a person to have the intention of doing whistleblowing. This study aims to determine whether Machiavellian nature and professional commitment affect the intention to do whistleblowing at the Jambi Province Youth and Sports Office. The data used are primary data obtained through questionnaires distributed to employees who work at the Jambi Province Youth and Sports Office and the research sample is 118 employees who work at the Jambi Province Youth and Sports Office with the sampling technique using the saturated sampling method. The data analysis method used multiple linear regression analysis using the SPSS program. The results of this study indicate that the Machiavellian nature and professional commitment affect the intention to do whistleblowing and it can be concluded that the higher the Machiavellian nature, the higher the intention to do whistleblowing as well as professional commitment, the higher the professional commitment, the higher the intention to do whistleblowing.